Lymphangioma of the vulva in a young woman, diagnosed previously as anogenital warts - Yulia N. Grekova; Natalya V. Zilberberg; Nina P. Toropova (LLC "MEDIAFORMAT", 2023)
Lymphangioma of the vulva is a rare benign tumor. Clinical manifestations in the form of papillomatous growths make differential diagnosis difficult and are often regarded as a herpes virus or papillomavirus infection. We present a clinical case of vulvar lymphangioma in a 19-year-old patient with an 8-year history of the disease, previously diagnosed as papillomavirus infection, for which cryodestruction was repeatedly performed without any visible effect. Clinically, the disease was manifested by multiple verrucous growths on the labia majora. A skin biopsy showed hyperplastic epidermis with hyperkeratosis, cavities lined with endothelium and filled with eosinophilic protein fluid. To date, there is no consensus on the optimal therapy for vulvar lymphangioma. The use of destructive methods is not always effective and the recurrence, rate remains high enough.